The Optimization of Performance of the Police Kamsel Unit Through Traffic Community Education to Reduce Traffic Violations at Kendal Police - Sinulingga, Marissa (Police Studies Review, 2024)
This research is motivated by the number of traffic violations in Kendal police station. That showed that the implementation of traffic community education activities and the performance made by the Kamsel Unit, especially in reducing traffic violations in the jurisdiction of the Kendal Police, were still not optimal. The purpose of this research is to describe the organizational resources of the police kamsel unit in implementation of traffic community education activities in reducing traffic violations in the jurisdiction of the Kendal Police and to describe system management of implementation of traffic community education activities in reducing traffic violations in the jurisdiction of the Kendal Police. The research location in this final project is the Kendal Police Station. To discuss this research, the author uses theories and concepts that are relevant to the existing problems as follows: Management theory, management process theory, SWOT theory (strength, weakness, opportunity, and threats, Traffic community education concept, traffic violations theory, and optimization theory. The research method used in this research is a qualitative approach and type of field research, primary and secondary data sources, data collection techniques with interviews, observation and document studies, data validity with source triangulation, techniques and time as well as data collection analysis techniques, data reduction, Presentation of data and Drawing Conclusions. The results of the study found that the efforts made by the Unit Kamsel through traffic community education were still not optimal because there were still traffic violations that occurred. The inhibiting factor internally is the lack of personnel and the quality of personnel, facilities and infrastructure as well as the activity budget, while externally the lack of public awareness to comply with traffic regulations. Based on the results of the study, the authors suggest that the Unit Kamsel in reducing traffic violations can maximize traffic education activities and make a new inovation for traffic community education to tell the audience and the leader should control the activity of traffic community education properly.